Quivers of Bound Path Algebras and Bound Path Coalgebras - Intan Muchtadi Alamsyah; Hanni Garmini (Journal of Mathematical and Fundamental Sciences, 2010)
Algebras and coalgebras can be represented as quiver (directed graph), and from quiver we can construct algebras and coalgebras called path algebras and path coalgebras. In this paper we show that the quiver of a bound path coalgebra (resp. algebra) is the dual quiver of its bound path algebra (resp. coalgebra).